STRATEGI DIPLOMASI PERLINDUNGAN PMI MELALUI MORATORIUM PEKERJA DI MALAYSIA: Indonesia - Siti Binik Rusmiati; Mohammad Louis Ardiansyah; Helga Yohana Simatupang (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study aims to analyze the Indonesian government's diplomatic strategy under the leadership of Foreign Minister Retno Marsudi in protecting Indonesian Migrant Workers (PMI) in Malaysia through moratorium on labor placement in 2020–2022. The focus of the study is on human rights violations against PMI, lack of transparency in recruitment systems such as the Maid Online System (MOS), and Malaysia non-compliance with the Memorandum of Understanding (MoU). This study uses descriptive qualitative method with data collection techniques through literature studies and analysis of official government documents. The analytical framework used is the concept of Protection Diplomacy by Vermeer-Künzli. The results show the moratorium imposed in July 2022 was effective coercive diplomatic instrument in pressuring the Malaysian government to respect the one-channel system. This policy reflects Indonesia's foreign policy priorities, which prioritize citizen protection. Through this strategy, it succeeded pushing for new agreement that better guarantees protection and rights of PMI. This study concludes that the moratorium is not administrative in nature, but rather a strategic negotiation tool to strengthen Indonesia's bargaining position in bilateral diplomacy.  The novelty of this research lies in the analysis of the integration of the PMI moratorium policy into the practice of protection diplomacy under Retno Marsudi's.